2020
DOI: 10.1177/1091581819900150
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Potentiates Ethanol-Induced Neurotoxicity Through mTOR/p70S6K/4E-BP1 Inhibition in SH-SY5Y Cells

Abstract: Caffeine is a popular psychostimulant, which is frequently consumed with ethanol. However, the effects of caffeine on neuronal cells constantly exposed to ethanol have not been investigated. Apoptosis and oxidative stress occurring in ethanol-induced neurotoxicity were previously associated with decreased phosphorylation of the mTOR/p70S6K/4E-BP1 signaling proteins. Evidence also suggested that caffeine inhibits the mTOR pathway. In this study, human SH-SY5Y neuroblastoma cells were exposed to caffeine after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These findings corroborate those from the literature, i.e., at 10 mM CAF, the enzymatic activity of caspase-3 might induce an apoptotic process [ 9 ], whereas in the concentration range between 10 and 100 μM CAF, cell apoptosis was prevented [ 11 ]. Sangaunchom and coworkers observed that 10 mM and 20 mM of CAF reduced the viability of SH-SY5Y to 75% and 34% of the untreated controls, respectively, after 24 h [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings corroborate those from the literature, i.e., at 10 mM CAF, the enzymatic activity of caspase-3 might induce an apoptotic process [ 9 ], whereas in the concentration range between 10 and 100 μM CAF, cell apoptosis was prevented [ 11 ]. Sangaunchom and coworkers observed that 10 mM and 20 mM of CAF reduced the viability of SH-SY5Y to 75% and 34% of the untreated controls, respectively, after 24 h [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…mTOR is co-regulated by Akt and AMPK and mTOR activity is indicated by its phosphorylation. A study found that mTOR regulated apoptosis of neuroblastoma cells mainly through regulation of its downstream targets p70S6K and 4E-BP1 [27]. Multiple phosphorylation sites are present on mTOR, Ser 2448 and Ser 2481 are the phosphorylation sites of mTORC1 and mTORC2, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…And the luciferase activity assay showed that caffeine could also induce the activation of HERV-W environmental promoter, improve the transcription level of syncytin-1, thus promoting the proliferation of NB cells [ 100 ]. Several studies suggested that caffeine could play roles in different pathways, such as releasing calcium stored [ 101 ], activating the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway [ 102 ], inhibiting cellular mTOR/P70S6K/4E-BP1 [ 103 ] or inducing vascular endothelial growth factor expression [ 104 ]. Secondly, treatment of the SK-N-DZ cell line with hypoxia-reoxygenation or DNA methylation inhibitor 5-azacytidine could increase the expression of syncytin-1 [ 99 ].…”
Section: Syncytin-1 and Tumorsmentioning
confidence: 99%